Diseases and insect pests status of commercially grown jujube in Bangladesh - Hoque, Mohammed Ziaul; Akanda, Abdul Mannan; Miah, Md Ismail Hossain; Bhuiyan, Md Khorshed Alam; Miah, Md Giashuddin; Begum, Farhana (Fundamental and Applied Agriculture, 2017)
Jujube is one of the important high value fruit crops of Bangladesh. Commercial cultivation of Jujube increased all over Bangladesh because of its high yield potential, nutritive value and high market price. But with the expansion of its cultivation, prevalence of diseases and insect pests increase significantly. For identification and management of those diseases and insect pests and to identify other Jujube related problems a comprehensive survey needs to be done for cultivating Jujube in an economic manner. A survey has been carried out to know the prevalence of diseases and insect pests of Jujube and their management status in five major Jujube growing areas of Bangladesh during three consecutive years. A total of seven problems were identified during survey of them diseases and insect pests’ attack was found as one of the major constraints for commercial cultivation of Jujube. The powdery mildew, fruit drop, fruit spot and rot, sooty mold, leaf rust and leaf spot were identified as common diseases of Jujube in the surveyed areas. Regarding pest infestation, a total of eleven insect pests were identified during survey and white spider mite reported first time on Jujube in Bangladesh. In terms of management aspects, Thiovit, followed by Bavistin, Contaf, Tilt, Companion and Score were observed as frequently used fungicides to control diseases in commercial orchards. The growers prefer alternate spray of more than one fungicide than single application. The effectiveness of fungicides was satisfactory with little variation as opined by the growers. In addition, Ripcord, Symbush, Emitaf, Cythrin, Furadan and Regent were commonly applied insecticides against insect pests. The use of chemicals by the growers was not satisfactory as per recommendation. The approximate loss due to powdery mildew disease was 25- 30%, it might be as high as 80-100% while control measures did not take in time. On the other hand, post-harvest disease loss was around 20-25%. For preparing good diseases and pests’ identification and management programs of Jujube in Bangladesh, above mention information will play significant role.